Effect of Occupational Stress on Employee Performance in Industrial City Division Mbale City - Wambi Paul (Uganda Christian University, 2024)
The study concentrated on the effect of occupational stress on employee performance in Industrial City Division Mbale City and it concentrated on the three specific objectives of: To examine the effect of overwork stress on employees‟ performance in Industrial City division of Mbale City, to find out the effect of over time stress on employees‟ performance in Industrial City division of Mbale City and to establish the effect of workplace conflict stress on employees‟ performance in industrial City Division of Mbale City. The study used a descriptive research methodology using both qualitative and quantitative. The study considered a sample size of respondents and study findings concluded that: Findings concluded that: low quality work is one of the effects of overwork stress on employee performance, that employees who want to make more money at any cost might create overtime by stalling work during the normal work day, that reduced employee motivation is an effect of stress on employee‟s performance, that overtime stress leads to anxiety and depression among employees, that increased risks of heart diseases and health complications that overworked employees suffer from low levels of initiatives and innovations, that workplace conflict stress consumes employees‟ emotional capacity, because they have limited emotional bandwidth to dedicate to thoughtful communication. The study recommend that: There should be more investments by different Governments in order to prevent work place stress and lastly that there is need for the Government to curry out sensitization programmes to different stake holders in order reduce on occupational stress challenges.